2019
DOI: 10.1186/s12877-019-1206-z
|View full text |Cite
|
Sign up to set email alerts
|

Lower dietary variety is a relevant factor for malnutrition in older Japanese home-care recipients: a cross-sectional study

Abstract: Background Nutritional status of the older people is affected by various life-style factors. Although dietary habit is one of the life-style factors, it is unknown which of older home-care recipients’ dietary habits are associated with malnutrition. The purpose of this study was to examine the association of dietary variety, as an evaluation index for dietary habits, with malnutrition in Japanese older home-care recipients. Methods This cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
1
25
1
2
Order By: Relevance
“…Our study also showed an indirect effect of the CCI on the MNA score. The correlation between malnutrition and comorbidities is well-known, and previous studies reported that malnourished older people have higher CCI scores (37,38). The most prevalent comorbidity found in the participants of the current study was dementia (29.5%).…”
Section: Discussionsupporting
confidence: 50%
“…Our study also showed an indirect effect of the CCI on the MNA score. The correlation between malnutrition and comorbidities is well-known, and previous studies reported that malnourished older people have higher CCI scores (37,38). The most prevalent comorbidity found in the participants of the current study was dementia (29.5%).…”
Section: Discussionsupporting
confidence: 50%
“…After title and abstract screening, 334 records were kept for full-text retrieval and 52 articles were included at full-text review−48 original studies ( Figure 1) and four Systematic Literature Reviews (13)(14)(15)(16). It should be noted that seven papers including older people with HDM in a broad sample were not included in the synthesis as separated data analyses were not conducted for HDM participants-analyses were done on a broader sample including participants without and with HDM (17)(18)(19)(20)(21)(22)(23). Unfortunately, we were not able to find the full text for 12 records despite that we tried to purchase them through the network of university libraries or to contact the authors.…”
Section: General Description Of the Systematic Review Article Selectionmentioning
confidence: 99%
“…Nine studies assessed the impact of an "improved" HDM service on nutritional outcomes compared to a regular service ( Table 5). Improvement consisted in providing energy and/or protein enriched meals and/or snacks [six studies: 21,44,45,49,56,64], in providing additional meals and/or snack (e.g., breakfast) to the regular offer (31,71), or in providing dietetic counseling (49).…”
Section: Impact Of An Improved Home-delivered Meal Service On Nutritimentioning
confidence: 99%
“…Good dietary habits are associated with better health status, especially among older adults. One essential aspect of diet quality is variety; older adults with a more varied diet have better nutritional status (1,2) . Previous gerontology studies used dietary variety as an index of diet quality and demonstrated the association between poor diet quality and health problems such as functional capacity (3) , cognitive decline (4) , sleep quality (5) , frailty (6) , muscular decline (7) and mortality (8) among older adults.…”
mentioning
confidence: 99%